Mutational analysis of trp-229 of human immunodeficiency virus type 1 reverse transcriptase (RT) identifies this amino acid residue as a prime target for the rational design of new non-nucleoside RT inhibitors. - Pelemans, H; Esnouf, R; De Clercq, E; Balzarini, J (2000)
Trp-229 is part of the non-nucleoside reverse transcriptase inhibitor (NNRTI)-binding pocket of HIV type 1 (HIV-1) reverse transcriptase (RT), and is also part of the "primer grip" of HIV-1 RT. Using site-directed mutagenesis, seven RT mutants were constructed bearing the mutations 229Phe, 229Tyr, 229Ile, 229His, 229Lys, 229Cys, and 229Gln. We found that all of the mutants showed severely compromised RNA- and DNA-dependent DNA polymerase activities (<2% of wild-type activity). The recombinant 229Phe and 229Tyr RT enzymes were among the mutant enzymes with the highest activity (0.7 and 1.1% of wild-type activity, respectively) and we evaluated these for resistance against several NNRTIs. No resistance was found for the 229Phe RT, but the 229Tyr RT showed a approximately 20-fold resistance against UC-781 and lower resistance against emivirine and nevirapine. Attempts to make recombinant virus strains bearing the single 229Phe or 229Tyr RT mutation failed. Experiments in which we varied the pentenyl ether substituent of the thiocarboxanilide UC-781 revealed that Trp-229 can be specifically targeted by NNRTIs and that an alkenyloxy group length of five atoms assures an optimal interaction of the thiocarboxanilides with Trp-229. Our findings indicate that Trp-229, when combined with other crucial immutable amino acids (i.e., Tyr-318), is an appropriate candidate for the targeted design of new NNRTIs.